Microencapsulated C-Phycocyanin decreases IL-17 gene expression in Peripheral Blood Mononuclear Cells (PBMCs): IL-17 gene expression and encapsulated C-Phycocyanin - Esmaeili, Fatemeh; Esmaeili, Behnaz; Mahmoud Reza Pourmand,; Salar Helchi,; Emamshoushtari, Mir Mehrshad; Pajoum Shariati, Farshid (Iranian Journal of Pharmaceutical Sciences, 2025)
Chronic inflammatory diseases are characterized by persistent immune responses in genetically predisposed individuals. Environmental factors trigger these responses and are often accompanied by increased inflammatory factors, such as inflammatory cytokines or oxidative stress. Phycocyanin (PC), a pigment extracted from Spirulina platensis, has anti-oxidant and anti-inflammatory properties and has been shown to have beneficial effects in patients with inflammatory disease. In this study, we aimed to evaluate the impact of both encapsulated and non-encapsulated forms of PC on the expression of Catalase, Superoxide dismutase 1 (SOD1), Superoxide dismutase 2 (SOD2), and IL-17 genes in peripheral blood mononuclear cells (PBMCs) obtained from healthy individuals. For the experiment, Spirulina platensis (Arthrospira) PCC9108 was obtained from the microalgae bank of the Science and Research Branch of Islamic Azad University in Tehran, Iran. The optimal non-toxic concentration of PC was determined using an MTT assay. PBMCs were isolated from the whole blood, cultured, and stimulated with phytohemagglutinin (PHA) (10 µg/ml) in either encapsulated or non-encapsulated PC form. Following 48 hours, the gene expression analysis was assessed using Real-time PCR. Multi-group analysis of Catalase, SOD1, SOD2, and IL-17 gene expressions between unstimulated cells and stimulated cells under different conditions (treated with a high or low concentration of non-encapsulated (NEC-PC) and encapsulated PC (EC-PC)) revealed no significant difference (P=0.06, P=0.5, P=0.3 and P=0.2, respectively). However, the pairwise analysis showed that encapsulated PC (1000µg/ml) significantly decreases the IL-17 level (p=0.05). Our findings indicated that a high concentration of encapsulated PC reduces IL-17 levels. The results may inform future clinical trials for patients with inflammatory and autoimmune diseases that involve inflammatory responses.